Multiple Roles of Hydrogen in Future Mobility - Barna Hanula; Virag Meszaros; László Csizmadia-Csiky (Chemical Engineering Transactions)
Sustainability and GHG reduction are the pivotal points of any future mobility. The European policymakers prioritised the BEV technology from 2035 onward. This decision was based on the universal consensus that the BEV technology offers the highest efficiency and that sufficient green energy will be available on time. In this study, the authors will analyse the feasibility of this concept. Due to the stochastic availability of renewable power, a reliable power supply requires adequate storage capacity at the necessary scale and time. The other universal statement is that the production of e-fuels is too inefficient to compete with BEV technology. Based on different publications, the authors are convinced that only chemical storage can fulfil the requirements nationally or globally. The inevitable first step of this energy conversion is water electrolysis, energised by renewables. The losses occurring during the production of green hydrogen are an unavoidable burden on green electricity production. Due to the availability of the produced hydrogen, these losses do not count toward producing e-fuels like methanol, methane, and ammonia. In that case, the baseline of any efficiency comparison alters, and alternative and e-fuels will severely challenge the BEV technology in multiple applications and locations. These fuels will allow further improvements in the ICE technology. The most important finding of this study is that the investigation of separated sub-systems will not deliver the optimum solution for mobility. Only a holistic approach considering the interactions between power generation, power storage, and propulsion technology leads to reliable answers, and hydrogen is the key element of the solution.